The Effect of a Novel Theanine Complex (JDS-MT-003) on Sleep in a Pentobarbital-Induced Sleep Model in Mice - Sylla, Sarah; Ojalvo, Sara; Komorowski, James; Orhan, Cemal; Tuzcu, Mehmet; Şahin, Nurhan; Şahin, Kazım (Wiley, 2020)
[Abstract Not Available]
Annual Meeting on Experimental Biology -- APR 04-07, 2020 -- San Diego, CA